Razelektritvena optična spektroskopija (GDOES) - Šmíd, Petr (Vakuumist, 2000)
In this paper the basic principle of glow discahrge optical emission spectrometry for depth profile analysis is described and some of the remaining problems with regard to quantification are discussed. Several applications of this technique are also presented.
Keywords: optična spektroskopija; preiskava materiala